Selective Leaching for the Recycling of Lithium, Iron, and Phosphorous from Lithium-Ion Battery Cathodes’ Production Scraps - Martina Bruno; Carlotta Francia; Silvia Fiore (Batteries)
The market for lithium iron phosphate (LFP) batteries is projected to grow in the near future. However, recycling methods targeting LFP batteries, especially production scraps, are still underdeveloped. This study investigated the extraction of iron phosphate and lithium from LFP production scraps using selective leaching, considering technical and economic aspects. Two leaching agents, sulfuric acid (0.25–0.5 M, 25 °C, 1 h, 50 g/L) and citric acid (0.25–0.5 M, 25 °C, 1 h, 70 g/L) were compared; hydrogen peroxide (3–6%vv.) was added to prevent iron and phosphorous solubilization. Sulfuric acid leached up to 98% of Li and recovered up to 98% of Fe and P in the solid residues. Citric acid leached 18–26% of Li and recovered 98% of Fe and P. Totally, 28% of Li was precipitated for sulfuric acid process, while recovery with citric acid did not produce enough precipitate for a characterization. Sulfur is the main impurity present in the precipitates. The total operative costs associated with reagents and energy consumption of the sulfuric acid route were below 3.00 €/kg. In conclusion, selective leaching provided a viable and economic method to recycle LFP production scraps, and it is worth further research to optimize Lithium recovery.